The effects of social media on the undergraduate students' academic performances - Mushtaq, Ahmad Jahed; Benraghda, Abdelmadjid (University of Nebraska - Lincoln, 2018)
Social Media are growing rapidly among the young generation all over the world. University age students widely engaged using Social Media. So, they will affect students personal and professional live. Thus, this study is designed to find out the positive and negative effects of social media on the academic performances of students in Alberoni University of Afghanistan. As quantitative approach was adapted to collect the relevant data of study, a number of 371 survey questionnaires were administered among the undergraduates in nine faculties of Alberoni University. Subsequently, SPSS software was applied to analyze the relevant data of the study. It was concluded that in despite of public views concerning the misuse of social media among students in the society, most of the students were interested to use social media positively for their educations. The positive impacts of social media among the undergraduates appeared to be higher as compared to negative impacts. However, results of ANOVA showed that there are no statistically significant differences between positive and negative impact of social media and students' academic achievements. Educators and students can use social media as informational and communication tools to ease and improve learning process.